Pengaruh Kepemimpinan Karismatik dengan Employee Engagement Sebagai Variabel Mediasi terhadap Kinerja dan Retensi Karyawan pada PT Diansurya Global Tangerang - Septian Fajar Hidayat; Yatimin Yatimin; Siti Maryama (Journal of Comprehensive Science, 2026)
This research is motivated by the increasing turnover rate, fluctuations in employee performance, and low levels of employee enthusiasm and engagement at PT Diansurya Global Tangerang. This study aims to analyze the effect of Charismatic Leadership on Employee Performance and Employee Retention with Employee Engagement as a mediating variable. This study uses a quantitative approach with a survey method by distributing questionnaires to 75 respondents determined from a population of 301 employees using the Slovin formula. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between variables in the research model. The results show that Employee Engagement has a positive and significant effect on Employee Performance (?= 0.671; t = 8.951; p= 0.000) and on Employee Retention (?= 0.398; t= 4.277; p= 0.000). Charismatic Leadership is proven to have a positive and significant effect on Employee Engagement (?= 0.759; t= 17.755; p= 0.000) and Employee Retention (?= 0.270; t= 2.632; p = 0.009). Mediation analysis shows that Employee Engagement fully mediates the relationship between Charismatic Leadership and Employee Performance (indirect ?= 0.509; t= 8.272; p= 0.000), and partially mediates the relationship between Charismatic Leadership and Employee Retention (indirect ?= 0.302; t= 4.204; p= 0.000). The structural model has strong explanatory power with R² values ??of 0.576 for Employee Engagement, 0.547 for Employee Performance, and 0.381 for Employee Retention. The Q² values ??are respectively 0.415 and 0.258 indicate good predictive ability of the model.